Transnational families: Cross‐country comparative perspectives. Issue 7 (23rd May 2018) - Mazzucato, Valentina; Dito, Bilisuma B.
Abstract: This special issue aims to address the gap in transnational families studies by identifying if there are common patterns and effects of transnational family life across countries and regions, using cross‐country comparative analyses. In this editorial introduction, we highlight the overarching themes emerging from seven papers, which employ new large‐scale surveys specifically designed to collect information about transnational family life across different Latin American, African, and Southeast Asian countries and China. We discuss how these comparative studies offer new ways of understanding transnational families by focusing on their prevalence, composition, the experiences of their members, and how these change over time. We also highlight how differing and changing notions of care over space and a person's lifetime influence how transnational families are created, reproduced, maintained, and experienced. In general, the issue as a whole emphasises the need to take structural factors in both sending and receiving contexts into account when studying the form that transnational families take, how this changes over time, and the general and specific gendered effects they have on different members.